Proteome approaches combined with Fourier transform infrared spectroscopy revealed a distinctive biofilm physiology in Bordetella pertussis - Serra, Diego Omar (2008)
Proteome analysis was combined with whole-cell metabolic fingerprinting to gain insight into the physiology of mature biofilm in Bordetella pertussis, the agent responsible for whooping cough. Recent reports indicate that B. pertussis adopts a sessile biofilm as a strategy to persistently colonize the human host. However, since research in the past mainly focused on the planktonic lifestyle of B. pertussis, knowledge on biofilm formation of this important human pathogen is still limited. Comparative studies were carried out by combining 2-DE and Fourier transform infrared (FT-IR) spectroscopy with multivariate statistical methods. These complementary approaches demonstrated that biofilm development has a distinctive impact on B. pertussis physiology. Results from MALDI-TOF/MS identification of proteins together with results from FT-IR spectroscopy revealed the biosynthesis of a putative acidic-type polysaccharide polymer as the most distinctive trait of B. pertussis life in a biofilm. Additionally, expression of proteins known to be involved in cellular regulatory circuits, cell attachment and virulence was altered in sessile cells, which strongly suggests a significant impact of biofilm development on B. pertussis pathogenesis. In summary, our work showed that the combination of proteomics and FT-IR spectroscopy with multivariate statistical analysis provides a powerful tool to gain further insight into bacterial lifestyles.